Optimizing Play-Based Learning for Early Childhood in the Digital Era - Abdurohman, M. (Sekolah Tinggi Agama Islam Kuningan, 2024)
Background: Play-based learning is a foundational approach in early childhood education that supports holistic child development. However, amid increasing digitalization, concerns have emerged regarding the impact of digital technologies on traditional play-based pedagogies, despite their potential educational benefits.Objective: This study aims to examine the optimization of play-based learning approaches in early childhood education within digital contexts by comparing traditional play-based learning, technology-integrated play, and hybrid approaches that combine both modalities.Method: This mixed-methods study involved 156 children aged 4–6 years from eight early childhood centers. Three pedagogical conditions were compared: traditional play-based learning, technology-integrated play, and hybrid approaches. Data were collected over eight months through developmental assessments, observational protocols, teacher surveys, and parent interviews. Quantitative analyses were conducted to evaluate developmental outcomes across conditions.Findings and Implications: Results indicated that hybrid approaches produced superior outcomes in cognitive (d = 0.82), social-emotional (d = 0.76), and creative development (d = 0.91) compared to technology-only conditions, while maintaining comparable results to enhanced traditional play. Technology-integrated play showed benefits in specific cognitive skills (e.g., spatial reasoning and problem-solving) but demonstrated reductions in social interaction quality (42%) and imaginative play complexity (38%). Optimal integration involved limiting screen-based activities to 20–25% of total play time, emphasizing open-ended digital tools, and ensuring teacher-facilitated rather than solitary technology use. These findings highlight the importance of balanced integration strategies, educator training in technology-enhanced pedagogy, developmentally appropriate digital materials, and evidence-based guidelines for technology use in early childhood settings.Conclusion: Play-based learning remains foundational for early childhood development in digital contexts. Technology should function as a supplementary tool rather than a replacement for traditional play, and its integration must be carefully structured to preserve the essential developmental functions of play while leveraging digital affordances.